Evaluasi Efek Teratogen Ekstrak Terpurifikasi yang Diisolasi dari Fraksi Etil Asetat Daun Surian (Toona sureni (Blume) Merr) - Suharti, Suharti; Yosmar, Rahmi; Fitriani, Ade; Almahdy, Almahdy (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X)
Evaluation of teratogenic effects of purified extract isolated fromethyl acetate fractionation of surian leaves (Toona sureni (Blume) Merr.) onwhite female fetus mice has been carried out. The extract was given to miceorally in solution at doses of 5, 10, and 20 mg/kg BW on 6th until 15th day ofpregnancy. On 18th day of pregnancy, laparatomy was performed, then two– third of fetuses were immersed in alizarin red solution and the remainingin Bouin’s solution. The analyzed parameters were the weight of pregnantmice, the number of fetuses, the weight of fetuses, skeletal malformation andmorphology. The result showed that malformations were not shown in dose of 5mg/kg BW, but in dose of 10 mg/kg BW from one mice found one fetus causedlate growth and death. While on dose 20 mg/kg BW, one mice was not death.